Dosimetric Comparison of Doses to Organs at Risk Using 3-D Conformal Radiotherapy versus Intensity Modulated Radiotherapy in Postoperative Radiotherapy of Periampullary Cancers: Implications for Radiation Dose Escalation - Bahl, Amit; Kapoor, Rakesh; Tomar, Parsee; Singh, Oinam Arun; Gupta, Rajesh; Sharma, Suresh C (JOP. Journal of the Pancreas, 2013)
Context Postoperative periampullary cancers with high risk features are managed with adjuvant chemo radiotherapy. Doses of 40-50 Gy have generally been used in conventional radiotherapy. Dose escalation with conventional radiotherapy has been restricted due to surrounding critical organs. Objective The objective of this dosimetric analysis was to evaluate the dose of radiation received by organs at risk using 3D conformal radiotherapy (3DCRT) and intensity modulated radiotherapy (IMRT). Methods Ten postoperative patients of periampullary cancers were selected for this dosimetric analysis. Planning CT scans films were taken with slice thickness of 2.5 mm and transferred to EclipseTM treatment planning system. The clinical target volume (CTV) included the postoperative tumor bed and draining lymph nodal areas. A 1 cm margin was taken around the CTV to generate the planning target volume (PTV). Critical structures contoured for evaluation included bowel bag, bilateral kidneys, liver, stomach and spinal cord. IMRT plans were generated using seven field coplanar beams and 3DCRT planning was done using one anterior and two lateral fields. A dose of 45 Gy in 25 fractions was prescribed to the PTV. Results V45 for bowel bag was 212.3±159.0 cc (mean volume ± standard deviation) versus 80.9±57.4 cc in 3DCRT versus IMRT (P=0.033). The V28 dose analysis for bilateral kidneys showed a value of 32.7±23.5 cc (mean volume ± standard deviation) versus 7.9±7.4 cc for 3DCRT versus IMRT, respectively (P=0.013). The D60 for liver using 3DCRT and IMRT was 28.4±8.6 Gy (mean dose ± standard deviation) and 19.9±3.2 Gy, respectively (P=0.020). Conclusions Doses to bowel bag, liver and kidneys was significantly reduced using IMRT leaving ample scope for dose escalation. Image: Dose volume histogram (DVH) comparing doses to organs at risk.